Comparative ligand structural analytics illustrated on variably glycosylated MUC1 antigen–antibody binding - Barnett, Christopher B.; Senapathi, Tharindu; Naidoo, Kevin J. (Beilstein Journal of Organic Chemistry, 2020)
When faced with the investigation of the preferential binding of a series of ligands against a known target, the solution is not always evident from single structure analysis. An ensemble of structures generated from computer simulations is valuable; however, visual analysis of the extensive structural data can be overwhelming. Rapid analysis of trajectory data, with tools available in the Galaxy platform, can be used to understand key features and compare differences that inform the preferential ligand structure that favors binding. We illustrate this informatics approach by investigating the in-silico binding of a peptide and glycopeptide epitope of the glycoprotein Mucin 1 (MUC1) binding with the antibody AR20.5. To study the binding, we performed molecular dynamics simulations using OpenMM and then used the Galaxy platform for data analysis. The same analysis tools are applied to each of the simulation trajectories and this process was streamlined by using Galaxy workflows. The conformations of the antigens were analyzed using root-mean-square deviation, end-to-end distance, Ramachandran plots, and hydrogen bonding analysis. Additionally, RMSF and clustering analysis were carried out. These analyses were used to rapidly assess key features of the system, interrogate the dynamic structure of the ligand, and determine the role of glycosylation on the conformational equilibrium. The glycopeptide conformations in solution change relative to the peptide; thus a partially pre-structuring is seen prior to binding. Although the bound conformation of peptide and glycopeptide is similar, the glycopeptide fluctuates less and resides in specific conformers for more extended periods. This structural analysis which gives a high-level view of the features in the system under observation, could be readily applied to other binding problems as part of a general strategy in drug design or mechanistic analysis.
Keywords: binding; conformation; Galaxy; glycoprotein; in silico

(untitled) - Afgan, E.; Baker, D.; Batut, B.; van den Beek, M.; Bouvier, D.; Čech, M.; Chilton, J.; Clements, D.; Coraor, N.; Grüning, B. A.; Guerler, A.; Hillman-Jackson, J.; et al. (Nucleic Acids Res., 2018)

Mass Spectrometry of Proteins: Methods and Protocols - Stewart, P. A.; Kuenzi, B. M.; Mehta, S.; Kumar, P.; Johnson, J. E.; Jagtap, P.; Griffin, T. J.; Haura, E. B. (The Galaxy Platform for Reproducible Affinity Proteomic Mass Spectrometry Data Analysis, 2019)

(untitled) - Davidson, R. L.; Weber, R. J. M.; Liu, H.; Sharma-Oates, A.; Viant, M. R. (GigaScience, 2016)

(untitled) - Bray, S. A.; Lucas, X.; Kumar, A.; Grüning, B. A. (J. Cheminf., 2020)

(untitled) - Barnett, C. B.; Aoki-Kinoshita, K. F.; Naidoo, K. J. (Bioinformatics, 2016)

(untitled) - Senapathi, T.; Bray, S.; Barnett, C. B.; Grüning, B.; Naidoo, K. J. (Bioinformatics, 2019)

Essentials of Glycobiology - Brockhausen, I.; Schachter, H.; Stanley, P. (O-GalNAc Glycans, 2009)

(untitled) - Kufe, D. W. (Oncogene, 2013)

(untitled) - Nath, S.; Mukherjee, P. (Trends Mol. Med., 2014)

(untitled) - Al-azawi, D.; Kelly, G.; Myers, E.; McDermott, E. W.; Hill, A. D. K.; Duffy, M. J.; Higgins, N. O. (BMC Cancer, 2006)

(untitled) - Williams, K. A.; Terry, K. L.; Tworoger, S. S.; Vitonis, A. F.; Titus, L. J.; Cramer, D. W. (PLoS One, 2014)

(untitled) - Ricardo, S.; Marcos-Silva, L.; Pereira, D.; Pinto, R.; Almeida, R.; Söderberg, O.; Mandel, U.; Clausen, H.; Felix, A.; Lunet, N.; David, L. (Mol. Oncol., 2015)

(untitled) - Teramoto, K.; Ozaki, Y.; Hanaoka, J.; Sawai, S.; Tezuka, N.; Fujino, S.; Daigo, Y.; Kontani, K. (Ther. Adv. Med. Oncol., 2017)

(untitled) - Song, W.; Delyria, E. S.; Chen, J.; Huang, W.; Lee, J. S.; Mittendorf, E. A.; Ibrahim, N.; Radvanyi, L. G.; Li, Y.; Lu, H.; Xu, H.; Shi, Y.; et al. (Int. J. Oncol., 2012)

(untitled) - Brockhausen, I. (EMBO Rep., 2006)

(untitled) - Movahedin, M.; Brooks, T. M.; Supekar, N. T.; Gokanapudi, N.; Boons, G.-J.; Brooks, C. L. (Glycobiology, 2017)

(untitled) - Brooks, C. L.; Schietinger, A.; Borisova, S. N.; Kufer, P.; Okon, M.; Hirama, T.; MacKenzie, C. R.; Wang, L.-X.; Schreiber, H.; Evans, S. V. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Humphrey, W.; Dalke, A.; Schulten, K. (J. Mol. Graphics, 1996)

(untitled) - Cross, S.; Kuttel, M. M.; Stone, J. E.; Gain, J. E. (J. Mol. Graphics Modell., 2009)

(untitled) - Chaffey, P. K.; Guan, X.; Chen, C.; Ruan, Y.; Wang, X.; Tran, A. H.; Koelsch, T. N.; Cui, Q.; Feng, Y.; Tan, Z. (Biochemistry, 2017)

(untitled) - Steen, P. V. d.; Rudd, P. M.; Dwek, R. A.; Opdenakker, G. (Crit. Rev. Biochem. Mol. Biol., 1998)

(untitled) - Jentoft, N. (Trends Biochem. Sci., 1990)

(untitled) - Kirnarsky, L.; Prakash, O.; Vogen, S. M.; Nomoto, M.; Hollingsworth, M. A.; Sherman, S. (Biochemistry, 2000)

(untitled) - Kriss, C. T.; Lou, B.-S.; Szabò, L. Z.; Mitchell, S. A.; Hruby, V. J.; Polt, R. (Tetrahedron: Asymmetry, 2000)

(untitled) - Chen, P.-Y.; Lin, C.-C.; Chang, Y.-T.; Lin, S.-C.; Chan, S. I. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Wu, W.-g.; Pasternack, L.; Huang, D.-H.; Koeller, K. M.; Lin, C.-C.; Seitz, O.; Wong, C.-H. (J. Am. Chem. Soc., 1999)

(untitled) - Danne, R.; Poojari, C.; Martinez-Seara, H.; Rissanen, S.; Lolicato, F.; Róg, T.; Vattulainen, I. (J. Chem. Inf. Model., 2017)

(untitled) - Lemmin, T.; Soto, C. (BMC Bioinf., 2019)

(untitled) - Kirschner, K. N.; Yongye, A. B.; Tschampel, S. M.; González-Outeiriño, J.; Daniels, C. R.; Foley, B. L.; Woods, R. J. (J. Comput. Chem., 2008)

(untitled) - Jo, S.; Kim, T.; Iyer, V. G.; Im, W. (J. Comput. Chem., 2008)

Advances in Protein Chemistry and Structural Biology - Jo, S.; Cheng, X.; Islam, S. M.; Huang, L.; Rui, H.; Zhu, A.; Lee, H. S.; Qi, Y.; Han, W.; Vanommeslaeghe, K.; MacKerell, A. D., Jr; Roux, B.; et al. (CHARMM-GUI PDB Manipulator for Advanced Modeling and Simulations of Proteins Containing Nonstandard Residues, 2014)

(untitled) - Park, S.-J.; Lee, J.; Qi, Y.; Kern, N. R.; Lee, H. S.; Jo, S.; Joung, I.; Joo, K.; Lee, J.; Im, W. (Glycobiology, 2019)

(untitled) - Park, S.-J.; Lee, J.; Patel, D. S.; Ma, H.; Lee, H. S.; Jo, S.; Im, W. (Bioinformatics, 2017)

(untitled) - Lee, J.; Cheng, X.; Swails, J. M.; Yeom, M. S.; Eastman, P. K.; Lemkul, J. A.; Wei, S.; Buckner, J.; Jeong, J. C.; Qi, Y.; Jo, S.; Pande, V. S.; et al. (J. Chem. Theory Comput., 2016)

(untitled) - Eastman, P.; Swails, J.; Chodera, J. D.; McGibbon, R. T.; Zhao, Y.; Beauchamp, K. A.; Wang, L.-P.; Simmonett, A. C.; Harrigan, M. P.; Stern, C. D.; Wiewiora, R. P.; Brooks, B. R.; et al. (PLoS Comput. Biol., 2017)

(untitled) - Huang, J.; MacKerell, A. D., Jr (J. Comput. Chem., 2013)

(untitled) - Michaud-Agrawal, N.; Denning, E. J.; Woolf, T. B.; Beckstein, O. (J. Comput. Chem., 2011)

(untitled) - Skjærven, L.; Yao, X.-Q.; Scarabelli, G.; Grant, B. J. (BMC Bioinf., 2014)

(untitled) - McGibbon, R. T.; Beauchamp, K. A.; Harrigan, M. P.; Klein, C.; Swails, J. M.; Hernández, C. X.; Schwantes, C. R.; Wang, L.-P.; Lane, T. J.; Pande, V. S. (Biophys. J., 2015)

(untitled) - Bray, S. A.; Senapathi, T.; Barnett, C. B.; Grüning, B. A. (bioRxiv, 2020)

(untitled) - Ramachandran, G. N.; Ramakrishnan, C.; Sasisekharan, V. (J. Mol. Biol., 1963)

(untitled) - Tubiana, T.; Carvaillo, J.-C.; Boulard, Y.; Bressanelli, S. (J. Chem. Inf. Model., 2018)